The Somaesthetic Dimension of the Chinese Qi Erotics - Ellen Y. Zhang (Eidos. A Journal for Philosophy of Culture, 2022)
Preview: /Commentary: Richard Shusterman, Ars Erotica: Sex and Somaesthetics in the Classical Arts of Love (Cambridge: Cambridge University Press, 2021), 436 pages./ Richard Shusterman is the not the first scholar in the West who introduces sex and sexuality in the Chinese tradition. Other scholars engaged in this theme include Robert van Gulik, Michel Foucault, Douglas Wile, and Fang Fu Ruan. Nevertheless, Shusterman is the first one who brings the topic from the perspective of somaesthetics and within a bigger context: the classical arts of love in different cultures. It should be noted that sex or sexuality has received little attention in the history of Western philosophy, and it is still not an easy topic to address in philosophical discourse today in the face of “the somatic turn” in recent decades. In contrast, sexual representation with reference to body consciousness has always been an important part of the Chinese philosophical and religious tradition, and Daoism in particular, as remarkably presented by Shusterman in the chapter “Chinese Qi Erotics: The Beauty of Health and the Passion for Virtue” (AE, 150-94). The term “qi-erotics” coined by Shusterman reflects well the unique nature of Chinese cultural interpretations of sexual practice in terms of a lived experience that combines ars erotica with a sexological science of health.